Avaliação de minerais e elementos traço na leishmaniose cutânea e sua correlação com a patogênese da doença - Oliveira, Caroline Sobotyk de (2019)
Leishmaniasis is a disease caused by parasites of the genus Leishmania and can manifest several clinical forms like localized, disseminated skin lesions or visceral form. The clinical result of a Leishmania spp. infection is variable and depends on several factors, both related to the parasite and to the host. Immunity or susceptibility to infectious-parasitic diseases is related to the nutritional status of the patient. In recent years, some research has correlated nutritional status and the presence or absence of minerals and trace elements with the severity of the disease, both for tegumentary and visceral leishmaniasis. This study aimed to identify and quantify changes in macro and microelements during the course of experimental infection by Leishmania (Leishmania) amazonensis and to evaluate its influence on the pathogenicity of the disease, correlating them with the parasite load, histopathological analysis and parameters oxidative stress. For this, BALB/c mice were inoculated with the promastigote forms of L. (L.) amazonensis in stationary phase of growth. The animals were divided into different groups and submitted to different clinical situations, simulating immunocompetent and immunocompromised hosts. Samples of blood, spleen, liver and kidney were collected and subjected to Inductively Coupled Plasma Optical Emission Spectroscopy analysis, histopathology, butyrylcholinesterase activity, myeloperoxidase, thiobarbituric acid reactive substances, superoxide dismutase, total thiols and glutathione peroxidase. It was possible to observe visceralization of the disease with histopathological lesions in several organs of the infected animals, as well as a decrease in the levels of zinc and manganese in the spleen of L. (L.) amazonensis infected animals and immunosuppressed by CD4+ T cell depletion when compared to the control group (P <0.05). However, no alteration in the oxidative stress parameters was observed evidencing the resistance of L. (L.) amazonensis protozoans to the antioxidant response of immunocompetent and immunosuppressed hosts.